Analisis Kinerja Keuangan Berdasarkan Peraturan Direktur Jenderal Perbendaharaan PER-36/PB/2016 (Studi Pada UPT Puskesmas Ngoro Pada Tahun 2021-2022) - Hazar, Dewi; Purwanti, Lilik (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to analyze the financial performance of Ngoro Community Health Center using financial ratios based on the Regulation of the Director General of the Treasury Number PER-36/PB/2016. This study involves primary data collected through documentation of the financial statements of Ngoro Community Health Center between 2021 and 2022 after BLUD (Regional Public Service Agency). The data are analyzed by calculating the ratio from which the scores are assessed, assessing financial performance categorized into Good, Fair, and Poor, then conducting a financial performance analysis from the ratio calculation. The results of this study exhibited that the financial performance of Ngoro Community Health Center in 2021 achieved Good criteria as indicated by the percentage of 86% (80 < TS ≤ 95), yet worsened to Fair criteria in 2022 as indicated by the percentage of 59% (56 < TS ≤ 68) due to the contemporaneous inventory accumulation and expense increase resulting in the escalating operational costs that prevent from generating maximum profits.